Rethinking tomorrow: A case study of Danish company Novozymes. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This case study aims to describe Novozymes' strongly embedded improvement culture and its tradition of employee inclusion. Novozymes is a biotech-based company, headquartered in Denmark and employing approximately 6, 000 people in 30 countries. Innovation and sustainability are core to Novozymes' business values and objectives. The business is also very open in its relations with others in its field with partnering seen as a key competency in the drive towards sustainability and to "effectively create and build businesses that can help change the world." Design/methodology/approach: – Novozymes also acknowledges the importance of driving innovation from the bottom up and understands that engaging with the shop floor is good for employees and good for productivity. Findings: – This case study describes Novozymes' strongly embedded improvement culture and its tradition of employee inclusion. This evolves round the key elements of engagement, communications, feedback, acknowledgment, training and self-steering teams. Originality/value: – The company acknowledges workplace innovation as an important idea and sees it evolving from their everyday activity. Where there is a constraint or a problem to solve and that calls for a change in the way that they operate or a new training requirement, they do not theorise about it but get on and do it.